Ukrainian market of the commercial real estate in time of crisis - Chornous, Galyna; Grabilina, Maryna (Publishing House of the Wrocław University of Economics, 2009)
Since the year 2000 Ukrainian market of primary real estate has increased quickly. Development of any such real estate market takes place according to the specific laws. The principle of recurrence is one of the most important principles. Ukraine’s participation in the processes of globalization exerts strong influence on the state of the Ukrainian economy and accordingly on the development of its certain links. It had been supposed before that the real estate market existed as an independent sector of economy and functions according to its laws. Now this sector is considered as an important factor in development of other sectors of economy and influences the development of domestic enterprises. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 484